Analysis of post-fire regeneration of a pine-oak forest under two exposure conditions - Ortíz-Cuevas, Yulia Abigail; Alanís-Rodríguez, Eduardo; Cristian Adrian; Mora-Olivo, Arturo; Molina-Guerra, Víctor Manuel; Manzanares-Miranda, Nelson (Ecosistemas y Recursos Agropecuarios, 2025)
The natural process by which vegetation recovers is known as regeneration and in plant communities, it can be studied after a disturbance such as forest fires. The objective of this study was to analyze the regeneration of tree and shrub species in a forest three years after a crown fire comparing two slope exposures. The study was developed in an area affected by a crown fire in April 2021 within the "Bosque Escuela" (School Forest) belonging to the Universidad Autonoma de Nuevo Leon, in Iturbide, Nuevo Leon. Sixty 10 x 10 m plots were established, distributed in two exposures in burned and non-burned sites (15 per combination). For each tree and shrub species, crown height and diameter were recorded. For each combination, the ecological parameters of absolute abundance, crown area, and importance value index were calculated. Ecological parameters were compared among conditions using the Kruskal-Wallis and Dunn's post hoc tests. Species richness and the effective species index (ESI) were calculated. Bray-Curtis similarity index was calculated among plant communities. The results indicate that the northern-unburned vegetation combination had the highest cover, abundance, and diversity, while the southern-burned vegetation combination had the lowest values for the ecological parameters. Furthermore, exposure largely limited the distribution of plant communities with respect to the disturbance condition caused by the fire.
Keywords: fire ecology; plant community; plant cover; Sierra Madre Oriental; slope exposure